CHEMISTRY IN THE INDUSTRY SYLVINITE ORES CRUSHING, CLASSIFYING AND DE-SLIMING PROCESSES - D. S. Isaboyeva (Bright Mind Publishing, 2025)
This in the article sylvinite ore crushing , classifying and de-sliming processes analysis Chemistry in the industry materials grinding process , especially sylvinite ore in separation big importance has . In the article ore of the composition granulometric and chemical analysis , grinding stages , enrichment processes and de-sludging efficiency studied . Sylvinite ore to factions separation and every one faction chemical composition , as well as hydrodewatering process technological features discussion Research has been done . results , sylvinite flotation and galurgia methods using enrichment effective to be optimal conditions for to determine help gives . Article chemistry and mining industry experts for useful to be , sylvinite ore again work processes in improvement application possible .
Keywords: Sylvinite ore grinding, Granulometric analysis, Chemical Analysis, Grinding stages, enrichment processes, Sludge removal, Fractions, Flotation method, Galurgia method, Potassium chloride, Sodium chloride.